Study of the Types of Molluscs Used by Communities, in Lake Sentani, Papua - Suriani Surbakti (Jurnal Moluska Indonesia, 2020)
The distribution of molluscs in Lake Sentani depends on their broad adaptability, dispersal ability, and zoogeographic history and ecological conditions. Ecological conditions in Papua have undergone many changes after the passage of special autonomy. A study on mollusk groups used by the community was carried in May-June 2018. Several government programs that require new land clearing for settlements, infrastructure development and agricultural areas have resulted in the conversion of sago forests, rivers, swamps, mangrove forests and lakes as places of interest. New settlements and shopping centers, consequently the degradation of Lake Sentani is unavoidable. Lake Sentani is currently under a lot of pressure from both internal and external factors. Some observers of lake ecology generally only conduct studies on water quality, but have not studied much of the fauna diversity, the potential of the lake's biological resources, let alone study the diversity of mollusc species and the types used by the community and the threat to the sustainability of the mollusk groups that are used. The public's understanding of the existence of Molluscs from an ecological and economic point of view has contributed greatly. From the survey results in Lake Sentani, the types used by the community are: Thiara sp. Pomacea canaliculata,  Pilsbryoconcha exilis, Bellamya sp, and Faunus sp. in the in-let area. Utilization of mollusk groups as a source of  family economy is also the second source of protein after fish, while in mountainous areas, certain types of mollusk  shells are still used as a legally valid medium of exchange locally.